INTEGRASI NEURO LINGUISTIC PROGRAMMING (NLP) PADA MAHASISWA DENGAN GANGGUAN DEMOTIVASI PENGERJAAN SKRIPSI - bahly; Sudirman, Ulfa Zahirah; Mujahidah Nurqalbi; Abel Widiastira (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Students' difficulties in completing their thesis due to continuous revisions, obstacles in the field and guidance that are considered difficult become a psychological burden that can develop into demotivation. If not overcome, difficulties will develop into demotivation, namely a decrease in the enthusiasm of students to complete their thesis. This research aims to: (1) integrate NLP in students who experience demotivation in thesis work and (2) develop a Neuro Linguistic Programming (NLP)-based resilience strategy guide that can be applied by students to overcome their demotivation in completing their thesis. This research used a qualitative approach with an action research design. The research subjects were active students of the Indonesian Language and Literature Education study program at Universitas Negeri Makassar who were selected using purposive sampling technique. NLP intervention was conducted through reframing, anchoring and visualization techniques with in-depth interviews as the main technique of data collection. Data analysis was conducted using the Interpretative Phenomenological Analysis (IPA) approach. The results showed that NLP is effective to help students overcome demotivation in thesis work. NLP helps students dialogue with themselves, visualize their success, and build enthusiasm starting from small things. Students can also apply resilience strategies, namely learning to manage emotions and seeking social support.